A green and low-cost hollow gangue microsphere/geopolymer adsorbent for the effective removal of heavy metals from wastewaters. (15th September 2019) - Yan, Shu; Zhang, Fanyong; Wang, Lu; Rong, Yedong; He, Peigang; Jia, Dechang; Yang, Jinlong
Abstract: In this paper, hollow gangue microspheres (GM) were introduced into a geopolymer matrix through a geopolymeric method; our aim was to synthesize a green and low-cost adsorbent (GM/KGP) for the removal of heavy metal ions (Cu 2+, Cd 2+, Zn 2+, and Pb 2+ ) from aqueous solutions. We investigated the microstructure of the GM/KGP adsorbent, as well as the effects of adsorbent dose, time, and temperature on adsorption behavior; moreover, an adsorption mechanism was proposed. The GM/KGP adsorbent possessed a typical broad amorphous structure and abundant O-containing functional groups on its surface. The adsorption of Cu 2+, Cd 2+, Zn 2+, and Pb 2+ onto the GM/KGP adsorbent fitted well to the pseudo-second-order kinetic model, while the equilibrium isotherm adsorption data were fitted well to the Langmuir equation. The adsorption mechanism GM/KGP was attributed to physical, chemical, and electrostatic attractions, as well as to ion exchange. We conclude that this novel adsorbent has great potential in removing heavy metal ions from contaminated wastewater. Graphical abstract: Image 1 Highlights: Porous GM/KGP adsorbent were synthesized by adding GMs into geopolymer matrix. Ion exchange and electrostatic attraction mechanisms were involved in adsorption. GM/KGP adsorbent has potential application in heavy metal ions wastewater treatment.